Radical humanism, the philosophy of freedom and democracy - Tarkunde, V. M. (Ajanta Publications : Distributors, Ajanta Book International, 1983)
Exposition of a sociopolitical concept, first propounded by Manabendra Nath Roy, 1893-1954, Indian political activist and thinker.